EDUCATION AS AN ELEMENT OF COMPETITIVENESS OF RURAL HOUSEHOLDS IN THE WIELKOPOLSKIE VOIVODSHIP - Sławomir Kalinowski (Acta Scientiarum Polonorum. Oeconomia, 2011)
In the era of globalization and economic integration, education constitutes a significant element of creating the value of human capital. Despite the fact that it is not possible to purchase it, and, only in some degree one may gain it as a result of increased education, it is vital to undertake the activities by governmental and non governmental organizations aiming at its quality improvement. Better educated people better operate on the market and easier adjust to changing market conditions. In rural areas of Wielkopolska only 4.2% of habitants have higher education, therefore it is necessary to undertake complementary activities by institutions dealing with education, solving and promoting different forms of replenishing job qualifications as well as constant education. The graduates should be equipped in capabilities indispensable in market economics, improving their competitiveness.